Jerzego, a new hisponine jumping spider from Borneo (Araneae: Salticidae) - Maddison, Wayne P.; Piascik, Edyta K. (Zootaxa, 2014)
A new genus and species of hisponine jumping spider from Sarawak, Jerzego corticicola Maddison sp. nov. are described, representing one of the few hisponine jumping spiders known from Asia, and the only whose male is known. Although similar to the primarily-Madagascan genus Hispo in having an elongate and flat body, sequences of 28s and 16sND1 genes indicate that Jerzego is most closely related to Massagris and Tomomingi, a result consistent with morphology. Females of Jerzego and other genera of Hisponinae were found to have an unusual double copulatory duct, which appears to be a synapomorphy of the subfamily. Two species are transferred from Hispo, Jerzego bipartitus (Simon) comb. nov. and Jerzego alboguttatus (Simon) comb. nov. Diagnostic illustrations and photographs of living spiders are provided.